Influence of backfill on coal pillar strength and floor bearing capacity in weak floor conditions in the Illinois Basin - Kostecki, T.; Spearing, Sam (Elsevier Ltd, 2015)
This paper discusses the current theoretical design equations associated with foundation design in the Illinois Basin, as well as the benefits of utilizing high density backfill in a numerical model, to improve pillar and floor stability. Based upon the results, Vesic's bearing capacity solution for a two layered soil tends to underestimate the true bearing capacity of a foundation, especially at higher friction angles and when footings are placed in close proximity. Minimizing the distance between adjacent foundations has shown an improvement in the ultimate bearing capacity of a foundation; however, placing the foundations in too close proximity has shown the foundations may behave as a single foundation and undergo appreciable settlement. A 10-40% increase in pillar strength and ultimate bearing capacity can be expected when a cohesive fill is used between 25 and 75% fill of the mined height, respectively. The non-cohesive nature of the simulated backfill showed little influence on increased pillar strength, even at higher fill ratios. It was determined, that as the shearing resistance, tensile strength and stiffness of the backfill are reduced, increases in coal pillar strength is due more to the confinement aspect of an underground mine rather than the strength properties of the material itself. A methodology for analyzing the plastic flow characteristics of a coal pillar and a footing using FLAC3D has also been presented herein.